Concrete durability and repair technology proceedings of the International Conference held at the University of Dundee, Scotland, UK on 8-10 September 1999 - Dhir, Ravindra K.; McCarthy, Michael J. 1965- (Thomas Telford, 1999)
This text covers recent developments in the areas of durability provisions, assessment and monitoring, and repairs. Specific topics discussed include, selection of materials and mix composition, performance specification and durability by intent.
"Proceedings of the three day international conference held during the Congress, Creating with Concrete ... organised by the Concrete Technology Unit, University of Dundee" _ Back cover.
Keywords: Concrete -- Deterioration -- Congresses.; Service life (Engineering) -- Congresses.; Concrete products -- Maintenance and repair -- Congresses.; elektronické knihy; electronic books